2006
DOI: 10.1074/jbc.m601759200
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Sites of Interaction between p23 and Hsp90 in Solution

Abstract: The co-chaperone p23 forms a complex with the chaperone Hsp90 that mediates the folding pathway leading to the production of functional steroid receptors. Solution NMR spectroscopy has been used to characterize sites of interaction between Hsp90 and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 41 publications
4
63
0
1
Order By: Relevance
“…ADP inhibits complex formation (Johnson & Toft, 1995;Sullivan et al, 1997) suggesting that p23 stabilizes the ATP bound form of Hsp90 and hydrolysis of ATP subsequently releases p23 from the complex. p23 binds directly to the NTD of Hsp90 although contacts are also made with Hsp90's MD Martinez-Yamout et al, 2006). The complex promotes or stabilizes the closed conformation and leads to the inhibition of the ATPase activity with inhibition observed for both yHsp90 and hHsp90 (McLaughlin et al, 2002;McLaughlin et al, 2006;Richter et al, 2004;Siligardi et al, 2004).…”
Section: P23 Arrests the Atpase Cycle Of Hsp90mentioning
confidence: 99%
“…ADP inhibits complex formation (Johnson & Toft, 1995;Sullivan et al, 1997) suggesting that p23 stabilizes the ATP bound form of Hsp90 and hydrolysis of ATP subsequently releases p23 from the complex. p23 binds directly to the NTD of Hsp90 although contacts are also made with Hsp90's MD Martinez-Yamout et al, 2006). The complex promotes or stabilizes the closed conformation and leads to the inhibition of the ATPase activity with inhibition observed for both yHsp90 and hHsp90 (McLaughlin et al, 2002;McLaughlin et al, 2006;Richter et al, 2004;Siligardi et al, 2004).…”
Section: P23 Arrests the Atpase Cycle Of Hsp90mentioning
confidence: 99%
“…Chemical shift mapping revealed that the co-chaperone p23, which stabilizes Hsp90-substrate complexes [182], binds to both the N-and the M-domain of Hsp90 in a 2:2 ratio [193,194]. This binding interface is also used by another co-chaperone, Aha1, which binds preferentially in an asymmetric way to the closed ATP-dimer, as revealed by chemical shift perturbations and biophysical analysis, leading to the closed form of Hsp90 [195,196].…”
Section: Hsp90mentioning
confidence: 99%
“…Therefore, we propose an alternative hypothesis that we feel conforms better to data reported in this investigation. Our hypothesis focuses on published results showing that Aha1 cochaperone competes with other early and late cochaperones for Hsp90 binding (4,6). Of particular interest is Sti1/Hop, which Ran et al (28) demonstrates is a positive regulator of MAL activator regulation.…”
Section: Aha1 Cochaperone Is a Negative Regulator Of Mal63 Mal Activamentioning
confidence: 99%
“…Conflicting reports suggest that the N-terminal domain of Aha1 and the full-length Hch1 activate Hsp90 ATPase activity, but the temperature-sensitive mutation of HSP82 used to isolate these suppressors does not exhibit a defect in ATPase activity at the nonpermissive temperature (4, 5, 18 -20, 24). The N-terminal domain of Aha1 binds to the middle region of Hsp90, and this binding competes with the binding of the early cochaperones Hop/Sti1 and p50/Cdc37 and the late cochaperone p23/Sba1, all cochaperones that inhibit Hsp90 ATPase suggesting other possible mechanisms of action (4,6,20). Most recently, a variety of in vitro and in vivo methods, including molecular footprinting and cross-linking, and structure-function mutation analysis of Aha1 were used to define sites of interaction between full-length mammalian Aha1 and Hsp90 (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation